Inosine supplementation has no effect on aerobic or anaerobic cycling performance - McNaughton, L.; Dalton, B.; Tarr, J. (International Journal of Sport Nutrition and Exercise Metabolism, 1999)
he two basic aims of this study were to add to the limited literature concerning Inosine as an ergogenic aid, and to determine the effects of Inosine supplementation over a period of 5 and 10 days, at a dosage of 10,000 mg á dÐ1 on measures associated with aerobic and anaerobic performance. Seven trained, volunteer male subjects (body mass = 63.0 ± 8.7 kg, VO2max = 67.9 ± 3.3 ml á kgÐ1 á minÐ1) participated in this study. The subjects completed three test sessions, each comprising three tests (5 3 6-s sprint, 30-s sprint, and 20-min time trial). Supplementation was carried out in a random, double-blind manner, and the test sessions were undertaken prior to (Baseline, B), on Day 6, and on Day 11. Blood was sampled prior to supplementation as well as on Days 6 and 11 and was analyzed for uric acid and 2,3 DPG. An analysis of the data indicated no performance benefit of supplementation and no improvement in 2,3 DPG concentration. Uric acid concentration increased significantly after both Days 6 and 11 (p < 0.03 and p < 0.004, respectively). It is concluded that Inosine has no ergogenic effects but may cause possible health problems if taken over long periods of time.